Withaferin A Induces Cell Death Selectively in Androgen-Independent Prostate Cancer Cells but Not in Normal Fibroblast Cells - Nishikawa, Yukihiro; Okuzaki, Daisuke; Fukushima, Kohshiro; Mukai, Satomi; Ohno, Shouichi; Ozaki, Yuki; Yabuta, Norikazu; Nojima, Hiroshi (PLOS ONE, 2015)
Withaferin A (WA), a major bioactive component of the Indian herb Withania somnifera, induces cell death (apoptosis/necrosis) in multiple types of tumor cells, but the molecular mechanism underlying this cytotoxicity remains elusive. We report here that 2 μM WA induced cell death selectively in androgen-insensitive PC-3 and DU-145 prostate adenocarcinoma cells, whereas its toxicity was less severe in androgen-sensitive LNCaP prostate adenocarcinoma cells and normal human fibroblasts (TIG-1 and KD). WA also killed PC-3 cells in spheroid-forming medium. DNA microarray analysis revealed that WA significantly increased mRNA levels of c-Fos and 11 heat-shock proteins (HSPs) in PC-3 and DU-145, but not in LNCaP and TIG-1. Western analysis revealed increased expression of c-Fos and reduced expression of the anti-apoptotic protein c-FLIP(L). Expression of HSPs such as HSPA6 and Hsp70 was conspicuously elevated; however, because siRNA-mediated depletion of HSF-1, an HSP-inducing transcription factor, reduced PC-3 cell viability, it is likely that these heat-shock genes were involved in protecting against cell death. Moreover, WA induced generation of reactive oxygen species (ROS) in PC-3 and DU-145, but not in normal fibroblasts. Immunocytochemistry and immuno-electron microscopy revealed that WA disrupted the vimentin cytoskeleton, possibly inducing the ROS generation, c-Fos expression and c-FLIP(L) suppression. These observations suggest that multiple events followed by disruption of the vimentin cytoskeleton play pivotal roles in WA-mediated cell death.